Consumption of Bottled Water by Children in the City of Bauru, State of SÃƒÆ’Ã‚Â£o Paulo, Brazil ÃƒÂ¢Ã¢â€šÂ¬Ã¢â‚¬Å“ A Brief Communication - Irene Ramires, DDS, MS; Roberto H. C. Grec, DDS; PatrÃƒÆ’Ã‚Âcia G. Moura, DDS; (Blackwell Synergy, 2007)
To determine the consumption of bottled water by children in the city of Bauru, State of São Paulo, Brazil. Methods: A stratified sample of the 17 areas established by the city plan was used to identify a total of 1,000 homes for visitation.